Namibia : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Namibia. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Namibia's GDP growth slightly moderated to 4.2 percent in 2014, largely owing to lower global demand for Namibia's main export commodities. Inflation remained contained, owing to low international commodity prices. The government's large-scale fiscal program contributed to job creation, and unemployment declined somewhat. Namibia's growth outlook is clouded with downside risks, while facing significant policy challenges. Its main policy challenges are therefore to strengthen its resilience to exogenous shocks and manage systemic risks in the financial sector, while promoting inclusive growth and job creation.